1995
DOI: 10.1002/j.1460-2075.1995.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

A universally conserved region of the largest subunit participates in the active site of RNA polymerase III.

Abstract: The largest subunits of the three eukaryotic nuclear RNA polymerase present extensive sequence homology with the beta' subunit of the bacterial enzymes over five major co‐linear regions. Region d is the most highly conserved and contains a motif, (Y/F)NADFDGD(E/Q)M(N/A), which is invariant in all multimeric RNA polymerases. An extensive mutagenesis of that region in yeast RNA polymerase III led to a vast majority (16/22) of lethal single‐site substitutions. A few conditional mutations were also obtained. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 46 publications
0
87
0
2
Order By: Relevance
“…1A) contains a 4-nt 3Ј-overhang at one end for factor-independent transcription (28) initiating with the dinucleotide primer GpA followed in turn by a run of 15 AMP residues, CMP ( 32 P-labeled), and the photoactive UMP analogue. We expected the initial run of weakly base-pairing A residues to result in reiterative slippage during repetitive addition of AMP to the initially synthesized RNA, generating a cluster of transcripts differing in length but with identical 3Ј ends (as previously encountered with E. coli RNA polymerase and also seen to occur with pol III (29,30)). The array of nascent transcripts contained within elongation complexes formed in the absence of UTP is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1A) contains a 4-nt 3Ј-overhang at one end for factor-independent transcription (28) initiating with the dinucleotide primer GpA followed in turn by a run of 15 AMP residues, CMP ( 32 P-labeled), and the photoactive UMP analogue. We expected the initial run of weakly base-pairing A residues to result in reiterative slippage during repetitive addition of AMP to the initially synthesized RNA, generating a cluster of transcripts differing in length but with identical 3Ј ends (as previously encountered with E. coli RNA polymerase and also seen to occur with pol III (29,30)). The array of nascent transcripts contained within elongation complexes formed in the absence of UTP is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The resulting halted ternary complexes contained a 17-mer RNA and were purified to remove rC11 and the NTPs (25,26). Traces of the 18-mer transcript remained, which could be attributed to a somewhat reduced cleavage efficiency of rC11 compared with the endogenous C11, and a negligible amount of a slippage product (27) was observed (Fig. 1B, lane 6).…”
Section: Resultsmentioning
confidence: 99%
“…S3B). Although these two positions are not directly engaged in the coordination of the Mg 2+ ions that participate in catalysis and can tolerate conservative substitutions (Dieci et al 1995), the structure of the RNAPII elongation complex has recently suggested a possible role for the first residue N in the specificity for ribo-rather than deoxyribonucleotide (Gnatt et al 2001). Whether the amino acid substitutions found at this position in NRPD1a and NRPD1b are indicative of a more relaxed specificity of the RNAPIV enzyme(s) toward the nucleotide substrate or reveal a more specific adaptation to novel function remains to be de- termined.…”
Section: Arabidopsis Expresses Two Class IV Largest Subunit Genesmentioning
confidence: 99%